The Activity Xylanase Enzyme Thermophilic Bacteria SSA 2 in Starter Variation - Elfah rahma; Irdawati Irdawati (Universitas Negeri Padang, 2021)
Xylanase is extracellular enzyme that hydrolyzes xylan into xylose and xylooligosaccharides. The bacteria that produce the xylanase enzyme, namely SSA 2 isolate from the Sapan River Aro Solok Selatan hot spring, has a temperature of 75ºC and a pH of 8 or alkaline. Thermophilic bacteria can produce xylanase enzymes under optimum environmental conditions. Environmental optimization can be done by optimizing media composition, dissolved oxygen content, aeration, agitation, starter concentration, pH and temperature. This study aims to determine the specific activity of the xylanse enzyme at the starter concentration. The starter concentrations used were 2%, 4%, 6%, 8% and 10%. The highest specific activity of the xylanse enzyme was at a starter concentration of 4% (0.916 U/mL) this indicates that a low starter concentration can lead to good microbial growth.